Prevalence and pattern of alcohol consumption among women of reproductive age group in urban settings of Sikkim: a cross sectional study - Konthoujam, Bemma; Kar, Sumit; Mehta, Vijay Kumar; Dutta , Sanjiba (International Journal Of Community Medicine And Public Health, 2023)
Background: Alcohol consumption by women of reproductive age group not only affects their health but can also cause multiple adverse birth outcomes. The objectives of the study were to assess the prevalence and pattern of alcohol consumption among women of reproductive age group in urban field practice areas of Sikkim Manipal Institute of Medical Sciences (SMIMS) by using a structured questionnaire and WHO tool, AUDIT (Alcohol Use Disorder Identification Test). Methods: The study was a cross sectional study. A total of 284 women of reproductive age group (15-49 years) were interviewed using a structured questionnaire and AUDIT. Results: The overall prevalence of alcohol consumption was 36.6%. Proportion of alcohol users was more among women of 25-34 years. Almost 95% of the women are current users (alcohol use in past 12 months). Beer was mostly preferred over other types of alcoholic beverages. Social customs (36.5%) and stress (25%) were the main reasons for consumption of alcohol. Based on AUDIT score, low risk drinking 68.6% was the predominant drinking pattern reported. However, one fourth of the women fall into hazardous pattern of drinking and 3 out of every 100 women had harmful and dependent pattern of drinking respectively. Conclusions: The present study highlights the prevalence of alcohol consumption among women of reproductive age group in urban field practice areas of SMIMS. Socio-cultural factors and stressful life plays an influential role in consumption of alcohol. Although low risk drinking is the predominant pattern of alcohol use, an alarming 31% of women consuming alcohol are at risk of developing alcohol related harm.